2016
DOI: 10.1038/nclimate3138
|View full text |Cite
|
Sign up to set email alerts
|

Day length unlikely to constrain climate-driven shifts in leaf-out times of northern woody plants

Abstract: (2016). Day length unlikely to constrain climate-driven shifts in leaf-out times of northern woody plants. Nature Climate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
210
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(231 citation statements)
references
References 44 publications
17
210
4
Order By: Relevance
“…The difference between S2 and S1 indicated that increasing photoperiod alone would exacerbate the advance of SOS across most of the NH (>98% (Figures S8a-S8d) and >99% ( Figures S8e-S8h), across all RCPs), especially at low latitudes (e.g., southern North America, the Tibetan Plateau) and in northern Europe. This finding not only confirmed the photoperiodic control of SOS (Caffarra, Donnelly, Chuine, & Jones, 2011;Körner & Basler, 2010;Zohner et al, 2016) but also suggested that the shorter days due to earlier SOS might restrict the advance of SOS in the future, particularly at lower latitudes, thus shaping the spatial pattern of a faster decrease in S T at low latitudes. This finding not only confirmed the photoperiodic control of SOS (Caffarra, Donnelly, Chuine, & Jones, 2011;Körner & Basler, 2010;Zohner et al, 2016) but also suggested that the shorter days due to earlier SOS might restrict the advance of SOS in the future, particularly at lower latitudes, thus shaping the spatial pattern of a faster decrease in S T at low latitudes.…”
Section: Determinations Of the Increasing Synchrony Of Spring Phenologysupporting
confidence: 59%
“…The difference between S2 and S1 indicated that increasing photoperiod alone would exacerbate the advance of SOS across most of the NH (>98% (Figures S8a-S8d) and >99% ( Figures S8e-S8h), across all RCPs), especially at low latitudes (e.g., southern North America, the Tibetan Plateau) and in northern Europe. This finding not only confirmed the photoperiodic control of SOS (Caffarra, Donnelly, Chuine, & Jones, 2011;Körner & Basler, 2010;Zohner et al, 2016) but also suggested that the shorter days due to earlier SOS might restrict the advance of SOS in the future, particularly at lower latitudes, thus shaping the spatial pattern of a faster decrease in S T at low latitudes. This finding not only confirmed the photoperiodic control of SOS (Caffarra, Donnelly, Chuine, & Jones, 2011;Körner & Basler, 2010;Zohner et al, 2016) but also suggested that the shorter days due to earlier SOS might restrict the advance of SOS in the future, particularly at lower latitudes, thus shaping the spatial pattern of a faster decrease in S T at low latitudes.…”
Section: Determinations Of the Increasing Synchrony Of Spring Phenologysupporting
confidence: 59%
“…The traditional view is that the seasonality in insolation and day length increases with latitude and, consequently, photoperiod at higher latitudes should provide a stronger signal than at lower latitudes (Saikkonen et al, ) in order to protect leaves and other tissues against, for instance, late frosts in the spring or other environmental stresses. Conversely, the study of Zohner et al () found, within the temperate biome, that species relying on photoperiod as a budburst signal were more commonly found at lower latitudes with shorter winters, whereas photoperiod‐sensitive budburst was rare at higher latitudes. Consequently, the understanding of how the geographical origin determines the degree of photoperiod sensitivity is unresolved.…”
Section: Introductionmentioning
confidence: 95%
“…The interplay between temperature and photoperiod (i.e., day length) affects phenological processes such as flowering time, budburst, seasonal stem growth, leaf senescence, and dormancy (Basler & Körner, ; Jackson, ; Luo et al, ; Rossi et al, ; Tylewicz et al, ; Way & Montgomery, ; Zohner, Benito, Svenning, & Renner, ; Zohner & Renner, ). Day length has also been documented to be a driver of seasonal changes in the photosynthetic capacity of leaves and ecosystems at similar or even larger importance as temperature (Bauerle et al, ; Bongers, Olmo, Lopez‐Iglesias, Anten, & Villar, ; Stinziano & Way, ; Stoy, Trowbridge, & Bauerle, ; Way, Stinziano, Berghoff, & Oren, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in temperate systems, cumulative growing degree days historically provided a reliable and adaptive indicator for the arrival of the growing season (Zohner et al. ), but warmer‐than‐average winter temperatures could lead to an early initiation of bud burst followed by damaging below‐freezing temperatures (Gu et al. 2008, Hufkens et al.…”
Section: Introductionmentioning
confidence: 99%